Chapter Paradigmi storiografici per insegnare la storia dell'educazione: riflessioni da una pratica di Public History - Salvarani, Luana (Studi e saggi, 2019)
Teaching the history of education to future educators? One possible way to avoid the sclerotization of the discipline into an excessive focus on handbooks is to conceive it as a public history practice, interrogating specific cases under the lens of different historiographic paradigms. The goal will then be to promote "historical thinking" in the future educator as a training ground for exercising doubt and critical citizenship.